Analysis of COVID-19-Related RT-qPCR Test Results in Hungary: Epidemiology, Diagnostics, and Clinical Outcome - Gombos, Katalin; Földi, Mária; Kiss, Szabolcs; Herczeg, Róbert; Gyenesei, Attila; Geiger, Lili; Csabai, Dávid; Futács, Krisztina; Nagy, Tamás; Miseta, Attila; Somogyi, Balázs Antal; Hegyi, Péter; et al. (Frontiers in Medicine, 2021)
Background: Effective testing is an essential tool for controlling COVID-19. We aimed to analyse the data from first-wave PCR test results in Hungary’s Southern Transdanubian region to improve testing strategies. Methods: We performed a retrospective analysis of all suspected COVID-19 cases between 17 March and 8 May 2020, collecting epidemiological, demographic, clinical and outcome data (ICU admission and mortality) with RT-qPCR test results. Descriptive and comparative statistical analyses were conducted. Results: Eighty-six infections were confirmed among 3,657 tested patients. There was no difference between the positive and negative cases in age and sex distribution; however, ICU admission (8.1% vs 3.1%, p=0.006) and in-hospital mortality (4.7% vs 1.6%, p=0.062) were more frequent among positive cases. Importantly, none of the initially asymptomatic patients (n=20) required ICU admission, and all survived. In almost all cases, if the first test was negative, second and third tests were performed with a 48-hour delay for careful monitoring of disease development. However, the positive hit rate decreased dramatically with the second and third tests compared to the first (0.3% vs 2.1%, OR=0.155 [0.053-0.350]). Higher E-gene copy numbers were associated with a longer period of PCR positivity. Conclusion: In our immunologically naïve suspected COVID-19 population, coronavirus infection increased the need for intensive care and mortality by 3-4 times. In the event of the exponential phase of the pandemic involving a bottleneck in testing capacity, a second or third test should be reconsidered to diagnose more coronavirus infections.